2006
DOI: 10.1002/ijc.22214
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the KIP family members p27KIP1 and p57KIP2 by SKP2 and the role of methylation in p57KIP2 inactivation in nonsmall cell lung cancer

Abstract: Knowing the status of molecules involved in cell cycle control in cancer is vital for therapeutic approaches aiming at their restoration. The p27 KIP1 and p57 KIP2 cyclin-dependent kinase inhibitors are nodal factors controlling normal cell cycle. Their expression in normal lung raises the question whether they have a mutual exclusive or redundant role in nonsmall cell lung cancer (NSCLC). A comparative comprehensive analysis was performed in a series of 70 NSCLCs. The majority of cases showed significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 63 publications
4
65
1
1
Order By: Relevance
“…Third, translocation of p57 Kip2 from the nucleus to the mitochondria was detected in live HeLa cells within 20 min after STS exposure. In fact, cytoplasmic localization for p57 Kip2 has been reported in non-small-cell lung carcinoma 20 and esophageal squamous cell carcinoma. 33 In addition, during osteoblast differentiation, cytoplasmic p57 Kip2 was found to inhibit LIM-kinase 1, a kinase involved in actin p57 Kip2 promotes apoptotic cell death P Vlachos et al filament dynamics, by translocating and sequestering it in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, translocation of p57 Kip2 from the nucleus to the mitochondria was detected in live HeLa cells within 20 min after STS exposure. In fact, cytoplasmic localization for p57 Kip2 has been reported in non-small-cell lung carcinoma 20 and esophageal squamous cell carcinoma. 33 In addition, during osteoblast differentiation, cytoplasmic p57 Kip2 was found to inhibit LIM-kinase 1, a kinase involved in actin p57 Kip2 promotes apoptotic cell death P Vlachos et al filament dynamics, by translocating and sequestering it in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…7 Taken together, these observations suggest that that p57 Kip2 exerts tissue-specific effects during development. Interestingly during adulthood, it has also been reported that p57 Kip2 expression is reduced in various tumors, [8][9][10][11][12][20][21][22][23][24] suggesting a possible function for this protein in tumorigenesis. Importantly, decreased p57 Kip2 expression may provide an important prognostic implication for patients with ovarian, hepatocellular and colorectal cancers, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In some experimental models, p57 Kip2 showed antiapoptotic activity, whereas other studies revealed no correlation between p57 Kip2 and apoptosis (47,102). Therefore, p57 Kip2 relevance in apoptosis is probably confined to specific conditions and cell types.…”
Section: P57 Kip2 Metabolismmentioning
confidence: 94%
“…In 2006, Pateras and colleagues (102) investigated p57 Kip2 content in 70 NSCLCs and identified a protein decrease (which was particularly evident in the nuclear compartment) in 89% of the cases. Functional studies showed that the reduction was due to methylation, allelic imprinting, and increased degradation (102). (133) analyzed 82 breast cancer samples for CDKN1C alterations.…”
Section: P57 Kip2 Content In Human Malignanciesmentioning
confidence: 99%
“…, most probably because of its Cdk inhibitory function, is frequently considered as a nuclear protein; however, cytoplasmic expression of this protein has been demonstrated in various tissue, tumors and derived cell lines (www.proteinatlas.org; Barbe et al, 2008;Nan et al, 2005;Matsumoto et al, 2000;Pateras et al, 2006;Bozdogan et al, 2008;Joseph et al, 2009). In fact, as for the other members of the family, p21…”
Section: Kip2mentioning
confidence: 99%